Investigating lexical diversity and lexical sophistication of productive vocabulary in the written discourse of Indonesian EFL learners - Juanggo, Willy (Universitas Pendidikan Indonesia, 2018)
This paper reports the findings in investigating lexical diversity and lexical sophistication of productive vocabulary in the written discourse of Indonesian EFL learners. Thirty one students at high school level participated in this study; 15 students were from B1 level and 16 students were from B2 level according to Common European Framework of Reference for Languages (CEFR). Studentsâ€™ written compositions were used as the main data for this study. The gauge was done based on the result of the calculation of lexical frequency profile (LFP). The result of the calculation showed that the lexical diversity index of students at higher level was greater than that of students at lower level. In addition, based on the calculation per LFP category, it was found that the two groups shared similar patterns of lexical diversity index in which most varied vocabulary used in their writings falls into the second most common 1000 wordlist, followed by vocabulary that belongs to â€œnot in the listsâ€ category and AWL, respectively. Subsequently, the first common 1000 words category became the least varied words used by the learners. In terms of lexical sophistication, it was found that the percentage of advanced vocabulary used by less proficient learners was slightly larger than the percentage of advanced vocabulary used by more proficient learners. However, there was no significant difference found between two groups of learners in terms of lexical diversity and lexical sophistication.